Tax policy as a toolkit on ensuring the conditions for the formation of a favourable business environment in a post-crisis economy - TYUPAKOVA, NINA NIKOLAEVNA; RYSALIEVA, MIRA SHARSHENKULOVNA; MERZHO, MUSA SHAMSUDINOVICH; SUGAROVA, IRINA VALERIEVNA; TUAEVA, NONA VALERIEVNA (The journal of contemporary issues in business and government, 2021)
The post-crisis development of the domestic economy brings into focus the need to find new sources of economic growth. One of the directions is the development of an effective tax policy. Exhausted potential of the economic growth model based on domestic and foreign demand is already evident. As a minimum, an immediate modification of the entire infrastructure of the financial and credit market is required. In these conditions, urgent proactive changes are needed; it is necessary to ensure transparency, provide effective tax incentives, increase the availability of credit and financial resources, etc. The group of key macroeconomic factors that negatively affect economic dynamics can be corrected by creating a set of priority tax policy instruments, which will neutralize the negative effect of dysfunctions of the financial system and ensure the business level and growth of investment activity in the national economy. The next global financial crisis aggravated by economic sanctions increased the impact of supranational institutions and increased the role and importance of state regulation in the Russian economy, and, first of all, in the field of tax institution activities. The importance of such coordination was shown as a result of the global economic crisis, the main reasons for which were systemic deficiencies in the implementation of regulatory macroeconomic policies; arbitrary use of innovative financial instruments; the chaotic development of aggressive lending technologies by commercial banks; improper use of methods for assessing investment risks, etc. The need for a theoretical and methodological study of modern tax policy structure in order to ensure a favourable business environment in the post-crisis economy prompted us to tackle this research topic.